Pengaruh Pelatihan, Pengembangan Karir, dan Motivasi Kerja terhadap Kinerja Karyawan di Perusahaan Outsourcing PT.XYZ - Situmorang, Desy Ermawati; Anatan, Lina (SAFE-Network, 2025)
This study aims to examine the influence of training, career development, and work motivation on employee performance at the outsourcing company PT. XYZ. The research adopts a quantitative approach. The analytical method used involves outer model and inner model testing. The analysis was conducted using the SEM-PLS technique with the aid of the SmartPLS 4 software. A total of 60 respondents participated in this study, all of whom are employees of the outsourcing company PT. XYZ. Based on the results of the analysis, the findings indicate that training has a positive but not significant effect on employee performance, career development has a negative and not significant effect on performance, and work motivation has a positive and significant effect on employee performance. The implication of these findings suggests that the company needs to provide relevant training programs tailored to employee needs on a regular basis, evaluate the effectiveness of career development programs by offering opportunities for contract employees to improve their employment status, and develop strategies to enhance employee motivation in order to improve overall performance.